Evaluation of innovative solutions for e-mobility. (30th April 2021) - Venticinque, Salvatore; Martino, Beniamino Di; Aversa, Rocco; Natvig, Marit K.; Jiang, Shanshan; Sard, Regina Enrich
This paper presents a methodology for the evaluation of innovative solutions designed by the GreenCharge project to advance electric mobility. The methodology is based on the CIVITAS evaluation framework and it is specialised according to the GreenCharge requirements. In particular, this paper provides an extensive list of Key Performance Indicators (KPIs) and which of them will be evaluated in three pilots to provide a quantitative estimation of impact of technology innovation. Evaluation will use automatic computation of data collected in pilots, simulation techniques and analysis of surveys and interviews. The paper describes how to deliver and how to present evaluation results. The detailed schedule of data collection and evaluation activities has been planned in collaboration with implementation activities. Finally, a preliminary requirement analysis of simulation and a dashboard design for KPIs presentation are discussed.